Diseño y Puesta En Marcha De Instalación Eléctrica Para Máquina Hielera AV400CR En Piscícola Berlín (2021)
To guarantee the cold chain in the production and transport process of tilapia for the company Piscícola Berlin S . A . S The support and accompaniment of the energy companies A&C ELECTRICIDAD INDUSTRIAL S . A . S and HAGESA GROUP S . A . S was requir ed for the design and implementation of an energy system as an account New that guarantees the correct operation of an Ice Machine type AV400CR. The work is based on a correct understanding and implementation of all the parameters, rules and norms that the E RETIE governs and that is required as a requirement for the supply of energy by lectrificadora del Huila (Electro Huila). The total energy demand was calculated from the data related to the location and the intensity of current required together with the knowledge of the operating modes of this equipment. From these data, the necessary power of the power supply, load transformation and the number of elements necessary for an adequate installation, measurement and distribution of energy was obtained.